Krypton-81 dating constrains timing of deep groundwater flow activation - Kim, J-H; Ferguson, G; Person, M; Jiang, W; Lu, Z-T; Ritterbusch, F; Yang, G-M; Tyne, R; Bailey, L; Ballentine, C; Reiners, P; McIntosh, J (Wiley, 2022)
Krypton-81 dating provides new insights into the timing, mechanisms, and extent of meteoric flushing versus retention of saline fluids in the subsurface in response to changes in geologic and/or climatic forcings over 50 ka to 1.2 Ma year timescales. Remnant Paleozoic seawater-derived brines associated with evaporites in the Paradox Basin, Colorado Plateau, are beyond the 81Kr dating range (>1.2 Ma) and have likely been preserved due to negative fluid buoyancy and low permeability. 81Kr dating of formation waters above the evaporites indicates topographically-driven meteoric recharge and salt dissolution since the Late Pleistocene (0.03–0.8 Ma). Formation waters below the evaporites (up to 3 km depth), in basal aquifers, contain relatively young meteoric water components (0.4–1.1 Ma based on 81Kr) that partially flushed remnant brines and dissolved evaporites. We demonstrate that recent, rapid denudation of the Colorado Plateau (<4–10 Ma) activated deep, basinal-scale flow systems as recorded in 81Kr groundwater age distributions.